2014
DOI: 10.1136/bmjopen-2014-006199
|View full text |Cite
|
Sign up to set email alerts
|

Radiologists’ perspectives about evidence-based medicine and their clinical practice: a semistructured interview study

Abstract: ObjectivesTo describe radiologist's attitudes and perspectives on evidence-based medicine (EBM) and their practice.DesignFace-to-face semistructured interviews, thematic analysis.Setting24 institutions across six Australian states and New Zealand. Transcripts were imported into HyperRESEARCH software and thematically analysed.Participants25 radiologists.ResultsSix themes were identified: legitimising decisions (validated justification, prioritising patient preferences, reinforcing protocols), optimising outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
1
9
0
1
Order By: Relevance
“…The European Association of Urology guidelines state that renal angiography is indicated only if spiral CTwith 3D reconstruction or MRA with reconstruction are not available (5,6). This information suggests that more strict guidelines may improve the confidence of radiologists in applying evidence-based medicine (29). Studies have shown subjective variation in how the literature is interpreted by individual clinicians (30).…”
Section: Discussionmentioning
confidence: 99%
“…The European Association of Urology guidelines state that renal angiography is indicated only if spiral CTwith 3D reconstruction or MRA with reconstruction are not available (5,6). This information suggests that more strict guidelines may improve the confidence of radiologists in applying evidence-based medicine (29). Studies have shown subjective variation in how the literature is interpreted by individual clinicians (30).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding physicians and EBM, generally many studies indicate physicians' positive attitudes towards the EBM and agree that practicing EBM improves patient care [4][5][6][7][8][9][10]. However, only about 50% of the physicians rated their clinical practices to be typically evidence-based [5,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Ainsi, en médecine, l'EBM permet certes de standardiser les pratiques, mais elle peut aussi conduire à la multiplication néfaste des protocoles, dont l'application s'avère parfois impossible à réaliser 16,17,29 . Car cette surprocéduralisation (en quantité et en niveau de précision) n'efface pas la variabilité des situations de travail !…”
Section: Les Démarches Classiques Engendrent De La Rigiditéunclassified